English-as-a-Second Languange Teachers' Reflections On in-Service Professional and Self-Development - Sulyman, Suraya (2005)
Teacher development (TD) is important in Malaysia. However, there is a lack of detailed study on teacher development specifically one that focuses on the self-development of individual teachers. The usual in-service training (INSET) evaluation questionnaire gave little indication as to the effectiveness of the teachers' development. Hence, this study is an attempt to show that reflection could be a more effective means to encourage teacher development. Reflection has been claimed to raise teachers' awareness of their own development and practice, but in general, rarely practiced. The purpose of the study was to explore and describe the ESL teachers' reflections on their reflective practice and experiences during the in-service training for smart school in promoting their self and professional development. Three research questions constructed to guide the study are: 1) How do ESL teachers describe themselves as being reflective teachers? 2) How do their reflections on the 12-week in-service training for smart school promote the teachers' self-development? 3) How do they relate their self-development to their professional development Five ESL teachers from secondary schools from the states of Selangor D a d Ehsan and Federal Territory had participated in the study. They were selected based on the number of years teaching English and their participation in a 12- week INSET for smart school. The primary research tools employed were interviews and journal writing. An interview protocol was constructed to guide the researcher. The interviews were tape-recorded and transcribed in verbatim. Observation of the training was carried out and recorded as field notes. A set of questionnaire to gather background and preliminary information was given to the respondents. The findings discovered that the respondents were aware of the importance of reflection and how it affected them positively in their self and professional development. However, the practice was infrequent and unsystematic; the respondents' analytical capability was limited in which the scope and depth of their reflection appeared narrow and shallow respectively. The contents of their reflections were predominantly descriptive with a few instances demonstrating dialogic reflection. The 12-week INSET for smart school activated teachers' reflective characteristics and enriched their personality making them more caring and open-minded; enabled them to reinforce the skills and knowledge and to reevaluate the effectiveness of their practice; the respondents preferred formal to informal teacher development activities to internalise new input; to learn new skills and acquire relevant materials for teaching; to communicate and share experiences and emulating the strategies used by the trainers. In the course of learning, they grew more self-confident, vocal, generous with their knowledge and skills and ready to lead. The teachers' desire to develop generally encouraged them to achieve better academic and professional positions. The respondents were independent English language learners whose interests, resourcefulness and involvement in extracurricular activities had shaped their beliefs and behaviour. Self-development to some extent has led to professional development. Consequently, each teacher has developed his or her own teaching style, refined personality and consistently enhancing their professional responsibilities. Incidentally, the study also uncovered external factors such as school culture, which involves teachers' working relationships and attitude, can both facilitate and obstruct the teachers' professional development. Overall, the findings of the study points that ESL teachers need to develop reflective habit in order to reflect constructively, one that will result in a more lasting development. This can be done through systematic training by integrating reflection exercises in all INSET courses and encouraging reflective practice in the workplace by creating positive and supportive conditions in schools.